Antidiabetic and Hepatoprotective Effects of Dichrostachys cinerea Bark Extract in Streptozotocin-Induced Diabetic Rats - Abudoleh, Suha Mujahed; Abualassal, Qais; Abudayeh, Zead Helmi; Ahmed, Zain Alabden Ghanim Ahmed; Hussein-Al-Ali, Samer Hasan; Ramalingam, Kowsalya; Narasimhamoorthi, Shilpa Perumal; Arulselvan, Palanisamy; Saravanan, Karunakaran; Sarathbabu, Subbarayan (Indian Journal of Pharmaceutical Education and Research, 2026)
Background: Diabetes mellitus is a complex metabolic disorder characterized by chronic hyperglycemia resulting from impaired insulin secretion, insulin action, or both. Persistent hyperglycemia is often accompanied by secondary complications, including hepatic dysfunction. Plant-based therapies continue to attract interest as potential adjuncts for managing diabetes and its associated complications. Objectives: The present study aimed to evaluate the antidiabetic and hepatoprotective effects of Dichrostachys cinerea bark extract in a Streptozotocin (STZ)- induced diabetic rat model. Materials and Methods: Diabetes was induced in male Wistar rats using streptozotocin (60 mg/kg, intraperitoneally). Animals were divided into five groups (n = 6): normal control, diabetic control, standard drug–treated (glibenclamide, 600 µg/kg), and two D. cinerea extract-treated groups receiving different oral doses. Following treatment, blood glucose levels and hepatic function markers-including Alanine Aminotransferase (ALT), Aspartate Aminotransferase (AST), Alkaline Phosphatase (ALP), Lactate Dehydrogenase (LDH), and total protein-were assessed to evaluate antidiabetic activity and hepatic status. Results: Administration of D. cinerea bark extract resulted in a significant reduction in blood glucose levels compared with the diabetic control group. Diabetic rats exhibited elevated hepatic enzyme levels, indicating liver dysfunction, which were markedly ameliorated following extract treatment. The observed biochemical improvements suggest a protective effect of the extract against diabetes-associated hepatic alterations. Conclusion: The findings demonstrate that D. cinerea bark extract exhibits antidiabetic activity and mitigates diabetes-associated hepatic enzyme disturbances in STZ-induced diabetic rats. These effects support its potential as a complementary therapeutic agent for diabetes-related hepatic complications. However, further studies involving phytochemical characterization, mechanistic investigations, and long-term safety evaluation are required before clinical application.
Keywords: Diabetes; Hepatotoxicity; Streptozotocin; Dichrostachys cinerea Bark Extract (DCBE)